Customary Forest Managements and Its Challenges in East Nusa Tenggara, Indonesia: An Implication of Constitutional Court Decision 2012 - Imam Budiman; Takahiro Fujiwara; Kazuhiko Harada; Noriko Sato (Jurnal Manajemen Hutan Tropika, 2021)
Customary forests have not been adequately recognized in state forest management in Indonesia for a long time. However, in the last decades, several fundamental policy changes occurred, and the roles of local communities significantly recognized in forest management. The forest tenure reforms for customary communities are actively addressed after the Constitutional Court Decision (CCD) Number 35 in 2012. The objectives of this study are (1) to determine the changes in customary forest management in response to the CCD and (2) to discuss policy challenges after the CCD in East Nusa Tenggara Province. This study employed qualitative descriptive analysis methods. The result showed the different responses of customary communities related to the institutional development towards CCD. The lack of local regulations regarding customary peoples' rights still need to be solved. Besides, the claims of customary communities for customary forests overlapping with state conservation areas and other customary forests can make the problem more complicated.